HUBUNGAN HIGIENE SANITASI DENGAN KEJADIAN INFEKSI Soil Transmitted Helminths PADA PEMULUNG DI TPS JATIBARANG - Lilik Setyowatiningsih; Surati Surati (Poltekkes Kemenkes Semarang, 2017)
SANITATION HYGIENE RELATIONSHIP WITH INFECTION SOIL TRANSMITTED HELMINTHS OF SCAVENGERS IN TPS JATIBARANG. Worming often be found in all parts of Indonesia, especially in conditions of poor sanitation and lack of hygiene individually. A deworming still causes much of the population in Indonesia by the Soil Transmitted Helminths (STH) is a group of intestinal nematode life cycle through the soil media. According to the Depkes, the prevalence of worm infection in 2006 for all ages in Indonesia between 40% -60%. The location of this research waste (TPS) in the Jatibarang region which is a central polling station in the city of Semarang with sanitary conditions of slums. The results of the study in 2005, known as much as 47.5% of scavengers in TPS Jatibarang experienced some worm infection and type of infection. Knowing the purpose of the research for sanitary hygiene related to infection Soil Transmitted Helminths TPS Jatibarang scavengers in the city of Semarang. Based on the research results, mainly scavengers TPS Jatibarang Semarang District has sanitation hygienic environment so well that the incidence of worm infection on a scavenger TPS Jatibarang 100% negative implemented. The data obtained are presented descriptive.